The raging storm - Cleeves, Ann (Cleeves, Ann. Two rivers series., 2023)
"Fierce winds, dark secrets, deadly intentions. When Jem Rosco-sailor, adventurer, and legend-blows into town in the middle of an autumn gale, the residents of Greystone, Devon, are delighted to have a celebrity in their midst. But just as abruptly as he arrived, Rosco disappears again, and soon his lifeless body is discovered in a dinghy, anchored off Scully Cove, a place with legends of its own. This is an uncomfortable case for Detective Inspector Matthew Venn. Greystone is a place he visited as a child, a community he parted ways with. Superstition and rumor mix with fact as another body is found, and Venn finds his judgment clouded. As the winds howl, and Venn and his team investigate, he realizes that no one, including himself, is safe from Scully Cove's storm of dark secrets" --